2003
DOI: 10.1213/01.ane.0000075838.91888.fe
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Uptake of Ropivacaine and Levobupivacaine in Rabbits

Abstract: Local anesthetic toxicity produced by an inadvertent IV injection is attenuated by the pulmonary uptake of local anesthetics. We compared the pulmonary uptake of ropivacaine and levobupivacaine after a bolus injection in rabbits. Sixteen anesthetized rabbits were randomly assigned to either a ropivacaine group or a levobupivacaine group. A bolus containing ropivacaine or levobupivacaine 0.5 mg/kg and indocyanine green (an intravascular indicator) 0.25 mg/kg was injected rapidly into the vena cava. Arterial blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This discrepancy between our study and others could be explained partly by the higher lipophilic property of levobupivacaine compared with ropivacaine, resulting in a higher pulmonary uptake. 21 This larger pulmonary uptake observed by Ohmura et al in anesthetized rabbits was associated with a lower maximal plasma level of levobupivacaine compared with ropivacaine. Nevertheless this was not observed in our study, where plasma levels were relatively similar and homogeneous during the first 4 minutes of IV infusion (Fig 5).…”
Section: Discussionmentioning
confidence: 88%
“…This discrepancy between our study and others could be explained partly by the higher lipophilic property of levobupivacaine compared with ropivacaine, resulting in a higher pulmonary uptake. 21 This larger pulmonary uptake observed by Ohmura et al in anesthetized rabbits was associated with a lower maximal plasma level of levobupivacaine compared with ropivacaine. Nevertheless this was not observed in our study, where plasma levels were relatively similar and homogeneous during the first 4 minutes of IV infusion (Fig 5).…”
Section: Discussionmentioning
confidence: 88%
“…Because the lungs are a large organ with complex pathways of transit and tissue uptake, they attenuate arterial blood drug concentrations and, to some extent, consequent risk of local anesthetic intoxication, whether from accidental intravenous administration or systemic absorption after perineural administration, 37,[45][46][47] , but by how much and for how long? Some examples of arterial and pulmonary arterial drug concentrations over a large range of levobupivacaine doses in the same sheep are shown in Figure 11.…”
Section: Dose Dependence Of Local Anesthetic Intoxicationmentioning
confidence: 99%
“…Stewart et al 296 observed in healthy volunteers that levobupivacaine and ropivacaine produced similar central nervous system and cardiovascular effects when given at equal concentrations, mg doses and infusion rates. Although traditional reports appear to suggest that ropivacaine has a greater margin of safety over both racemic and L-isomer bupivacaine, similar toxicity profiles may be the result of differences in systemic absorption; Ohmura et al 297 observed that the pulmonary uptake of ropivacaine was less than that of levobupivacaine in a rabbit model, which may offset any direct cardiac advantages. When local anesthetic toxicity occurs, continuous mixed venous oxygen saturation appears to provide, at least in dogs, an earlier and better detection monitor than mean blood pressure in assessing cardiac output.…”
Section: Complications Of Anesthesiamentioning
confidence: 98%